PERAN GURU DALAM MENINGKATKAN DAYA HAFAL SISWA MELALUI METODE TALQIN PADA MATA PELAJARAN PAI (Studi Deskriptif Kualitatif Pada Materi AlQur`An Kelas V SDN Indihiang Kota Tasikmalaya) - Rowi Karim, Aja; Imas Rodiah (Program Studi Pendidikan Agama Islam, 2023)
The purpose of this research is to find out the role of the teacher and the advantages and disadvantages of applying the Talqin method in increasing students' memorization of the AlQur`an Islamic Islamic Education subject in class V SDN Indihiang Kota. Tasikmalaya. The research method used in this research is qualitative descriptive, namely research that aims to systematically describe the facts found in the field, are phenomenal, and are not in the form of numbers, especially about the teacher's role in increasing students' memorization through the Talqin method in Subjects PAI material of the Qur'an. The results of the application of the talqin method to learning tahfidz Al-Qur`an itself, many children memorize quickly, the better and smoother their memorization. and have reached the specified target memorization. The advantage of applying the talqin method to PAI learning of Al-Qur`an material itself is to make it easier for children who, even though they cannot yet read and write the Al-Qur`an, can memorize it. The weaknesses in applying the talqin method to PAI learning of Al-Qur`an material are the difficulty in conditioning children, they are busy playing alone so that it interferes with learning, the time it takes to use this method is quite long, and the teacher himself must master reading Al-Qur`an so as not to run into trouble